Tinjauan Literatur Sistem Peringatan Fase Hijau: Efisiensi dan Keselamatan pada Simpang Bersinyal - Ratnasari Ramlan; Jurair Patunrangi; Ismadarni; Rizki Amaliah; Tri Wahyuningsih (Universitas Kristen Indonesia Paulus, 2025)
Signalized intersections are critical components of urban traffic systems. However, inefficiencies caused by start-up lost time (SULT) and increased accident risks remain major challenges. Green Phase Warning Systems (GPWS) have emerged as an Intelligent Transportation System (ITS) innovation to reduce SULT and improve traffic safety. This paper presents a literature review of GPWS research published from 2010 to 2025. Findings show that GPWS reduces driver reaction time by 15–25%, increases intersection throughput up to 20%, and decreases rear-end collision risks. However, its effectiveness in heterogeneous traffic contexts, particularly in Indonesia where motorcycles dominate, remains limited. Future studies should focus on adaptive GPWS designs tailored for mixed traffic and explore policy frameworks supporting large-scale adoption.